Peran Tumbuhan Berbunga sebagai Media Konservasi Artropoda Musuh Alami - Nia Kurniawati; Edhi Martono (Jurnal Perlindungan Tanaman Indonesia, 2015)
Flowering plants are plants with the ability to attract a lot of insects and other plant-loving organisms, as they possess various functions for these organisms, for instance as feed sources, ovipositions’ sites, or hiding places out of danger (refugia). Their varied functions make flowering plants to play important roles as special habitats for insects and other organisms. Their presence needs to be considered especially in agricultural land where the dominant planting pattern is monoculture, such as rice fields. The presence of flowering plants themselves will invite many different organisms playing their parts not only as herbivores, but also as natural enemies, pollinators and other ecologically important organisms. The faunal diversity stimulated by flowering plants will create more stable ecosystem, which in turn will keep the ecosystem components’ balance in check. The presence of flowering plants are therefore essential to the conservation of natural enemies in some particular ecosystem, such as agroecosystem. INTISARITumbuhan berbunga merupakan tumbuhan yang berkemampuan memikat banyak serangga dan jasad pemanfaat tumbuhan lainnya, dan memiliki banyak manfaat bagi jasad-jasad ini, misalnya sebagai sumber pakan maupun tempat perhentian (untuk meletakkan telur atau menyembunyikan diri dari bahaya). Fungsi yang beragam ini menyebabkan pentingnya memperhatikan tumbuhan berbunga sebagai habitat khusus bagi serangga dan jasad lainnya, terutama di pertanaman yang selama ini dominan sebagai ekosistem monokultur, misalnya pertanaman padi. Adanya tumbuhan berbunga akan mengundang berbagai jenis jasad yang dalam ekosistem tersebut memiliki bermacam-macam peran selain sebagai herbivora, misalnya sebagai musuh alami, polinator atau fungsi ekologis lainnya. Keberagaman fauna karena adanya tanaman berbunga akan menyebabkan terbentuknya ekosistem yang lebih stabil, yang pada gilirannya akan menjaga terjadinya keseimbangan komponen ekosistem. Kehadiran tumbuhan berbunga dengan demikian sangat penting untuk melestarikan populasi musuh alami di suatu ekosistem seperti agroekosistem.